2006
DOI: 10.1352/0047-6765(2006)44[128:hicods]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Health Insurance Coverage of Direct Support Workers in the Developmental Disabilities Field

Abstract: There is mounting evidence that employer-provided health insurance is an important factor in recruiting and retaining a competent and motivated direct support workforce within health and human services occupations. A review of the literature in this area, including new information related to the developmental disabilities field, is presented to assist nonprofit employers and government officials in designing initiatives to address increasing health care costs. Approaches to financing health coverage for frontl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Employer provided health insurance is a critical factor in recruiting and retaining DSPs [Ebenstein, 2006]. Most organizations offer health insurance benefits to some DSPs [Larson et al, 2005c].…”
Section: Wages and Benefitsmentioning
confidence: 99%
“…Employer provided health insurance is a critical factor in recruiting and retaining DSPs [Ebenstein, 2006]. Most organizations offer health insurance benefits to some DSPs [Larson et al, 2005c].…”
Section: Wages and Benefitsmentioning
confidence: 99%
“…By contrast, the mean hourly wage in 2007 for physicians was more than $70 per hour 30. Most low-income workers cannot afford health insurance premiums and copayments, even when coverage is offered by their employer 12,31,32. On the basis of a review of studies on characteristics of direct care workers and the wages and health insurance benefits available, Stone reported that most home care workers earning low incomes cannot afford health insurance 31…”
Section: Discussionmentioning
confidence: 99%
“…The Kaiser Family Foundation reported that the uninsured rate among workers in the health and social services industry was 23% in 2007 11. On the basis of a review of the literature in the health and human services occupations, Ebenstein concluded that the health insurance plans offered to direct care workers in the developmental disabilities field are “inferior … with less coverage and more out-of-pocket expenses” and that fewer direct care workers “are able to afford health coverage even if they are eligible.”12(p132)…”
mentioning
confidence: 99%
“…Yet there is mounting evidence that employer-provided health insurance is an important factor in recruiting and retaining a competent and motivated direct support workforce within health and human services occupations (see Ebenstein, 2006, for a review of the literature). Between 40% and 45% of all paraprofessional home care workers lack health care coverage, signifi cantly undermining the fi nancial stability of home care workers and their families (Feinberg, Hunt, Dawson, Braunstein, & Cameron, 2004).…”
mentioning
confidence: 99%